2012
DOI: 10.1155/2013/908340
|View full text |Cite
|
Sign up to set email alerts
|

Role of CA‐EDTA on the Synthesizing Process of Cerate‐Zirconate Ceramics Electrolyte

Abstract: The role of a combination between citric acid (CA) and ethylenediaminetetra acetic acid (EDTA) as chelating agents in preparation of BaCe0.54Zr0.36Y0.1O2.95powder by a modified sol-gel method is reported. The precursor solutions were prepared from metal nitrate salts (M+), chelating agents (C), and ethylene glycol (EG) at molar ratio of M+ : C : EG = 3 : 2 : 3. Chemical and phase transformation of samples during thermal decomposition were analyzed by thermogravimetric analysis (TGA) and Fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Meanwhile, the presence of secondary phases in S4 impurities of CeO 2 , (Ce,Zr)O 2 and BaCO 3 were observed in the XRD pattern. As reported in previous work, at this calcination temperature, the powder still consist remaining carbonate residue [7]. For the pellet sintered at 1300°C, the BaCO 3 impurity was decomposed and subsequently impeded a complete formation of BCZY.…”
Section: Phase Identificationsupporting
confidence: 75%
“…Meanwhile, the presence of secondary phases in S4 impurities of CeO 2 , (Ce,Zr)O 2 and BaCO 3 were observed in the XRD pattern. As reported in previous work, at this calcination temperature, the powder still consist remaining carbonate residue [7]. For the pellet sintered at 1300°C, the BaCO 3 impurity was decomposed and subsequently impeded a complete formation of BCZY.…”
Section: Phase Identificationsupporting
confidence: 75%
“…4) showed that the final weight loss occurred at a lower temperature for the EDTA-CA combination than for CA alone. It has previously been shown by Abdullah et al that in the sol-gel synthesis of BaCe0.54 Zr0.36 Y0.1 O2.95, gels prepared with an EDTA-CA combination exhibited lower thermal decomposition temperatures than gels prepared with EDTA or CA alone [38]. It was argued that the combination acted as a better combustion reagent to increase the reaction rate.…”
Section: Discussionmentioning
confidence: 98%
“…There are several sol-gel syntheses of perovskites reported in the literature in which EDTA and CA are used in combination, and many of them involve basic cations, such as Sr, Ba and La [38][39][40][41][42][43]. The interaction of EDTA and CA is clearly favourable for the formation of metal-organic precursor gels for these perovskite materials, although the mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Hence this can explain why DTPA proved to be a better complexing agent than EDTA when not combined with CA. There are several sol-gel syntheses of perovskites reported in the literature in which EDTA and CA are used in combination, and many of them involve basic cations, such as Sr, Ba and La [37][38][39][40][41][42] . The interaction of EDTA and CA is clearly favourable for the formation of metal-organic precursor gels for these perovskite materials, although the mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown by Abdullah et al that in the sol-gel synthesis of BaCe0.54 Zr0.36 Y0.1 O2.95, gels prepared with an EDTA-CA combination exhibited lower thermal decomposition temperatures than gels prepared with EDTA or CA alone. 37 It was argued that the combination acted as a better combustion reagent to increase the reaction rate. As in our synthesis, Abdullah et al did not observe any weight loss by TGA after 750 °C, but 1100 °C was necessary to obtain phase purity.…”
Section: Discussionmentioning
confidence: 99%